Dynamic contrast‐enhanced MRI: Use in predicting pathological complete response to neoadjuvant chemoradiation in locally advanced rectal cancer. Issue 3 (5th February 2015) - Tong, Tong; Sun, Yiqun; Gollub, Marc J.; Peng, Weijun; Cai, Sanjun; Zhang, Zhen; Gu, Yajia
<x xml:space="preserve">Abstract</x> Purpose To determine the ability of dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) to predict pathological complete response (pCR) before preoperative chemoradiotherapy (CRT) in locally advanced rectal cancer. Materials and Methods In a prospective clinical trial, 38 enrolled patients underwent pre‐ and post‐CRT DCE‐MRI at 3.0T. The tumor length and the following perfusion parameters (Ktrans, kep, ve) were measured for the tumor and compared between the pCR group and the non‐pCR group, as well as before and after CRT. For categorical variable comparison, the Kruskal‐Wallis test was used. P < 0.05 was considered significant. Results No difference in tumor length was found between the pCR and non‐pCR group pre‐ and post‐CRT (P = 0.26 (0.15, 0.45), 0.35 (0.21, 0.52), respectively). Before CRT, the mean tumor Ktrans in the pCR group was significantly higher than in the non‐pCR group (P = 0.01). A Ktrans of 0.66 emerged as the best cutoff for distinguishing pCR from non‐pCR. Regarding kep and ve, significant differences were also observed between the pCR and non‐pCR groups (P = 0.02, 0.01, respectively). The mean Ktrans, kep, and ve values post‐CRT were lower in the pCR group than in the non‐pCR group, although there was no significant difference (P = 0.10 (0.04, 0.16), 0.11 (0.07, 0.26), 0.10 (0.06, 0.23), respectively). Conclusion Before neoadjuvant chemoradiotherapy in rectal cancer, DCE‐MRI can distinguish between complete and incomplete response using a Ktrans threshold of 0.66 with a sensitivity of 100%. J. Magn. Reson. Imaging 2015;42:673–680.